Unique Case Reports Associated with Ovarian Failure: Necessity of Two Intact X Chromosomes - Lakshmi Rao Kandukuri; Venkata Padmalatha; Murthy Kanakavalli; Raseswari Turlapati; Mangalipally Swapna; Metuku Vidyadhari; Govindaraghavan Saranaya; Kattera Himaja; Mamata Deenadayal; Bipin Kumar Sethi; Prasun Deb; Nalini Gupta; et al. (Case Reports in Genetics)
Premature ovarian failure is defined as the loss of functional follicles below the age of 40 years and the incidence of this abnormality is 0.1% among the 30–40 years age group. Unexplained POF is clinically recognized as amenorrhoea (>6 months) with low level of oestrogen and raised level of Luteinizing Hormone (LH) and Follicle Stimulating Hormone (FSH > 20 IU/l) occurring before the age of 40. It has been studied earlier that chromosomal defects can impair ovarian development and its function. Since there is paucity of data on chromosomal defects in Indian women, an attempt is made to carry out cytogenetic evaluation in patients with ovarian failure. Cytogenetic analysis of women with ovarian defects revealed the chromosome abnormalities to be associated with 14% of the cases analyzed. Interestingly, majority of the abnormalities involved the X-chromosome and we report two unique abnormalities, (46,XXdel(Xq21-22) and q28) and (mos,45XO/46,X+ringX) involving X chromosome in association with ovarian failure. This study revealed novel X chromosome abnormalities associated with ovarian defects and these observations would be helpful in genetic counseling and apart from, infertility clinics using the information to decide suitable strategies to help such patients.